FLORA AND VEGETATION DIVERSITY IN THE INTERFLUVIUM NAPO-PUTUMAYO-AMAZONAS, PERU - ZÁRATE-GÓMEZ, Ricardo (2020)
The Napo-Putumayo-Amazonas interfluvium in the Peruvian Amazon harbors a great diversity of plant species and types of vegetation that are greatly needed by the rural Amazonian population for subsistence and commercialization. Understanding plant diversity can possibly contribute to the creation of conservation strategies that regulate their usage. Therefore, the objectives of this study were to evaluate the diversity of flora and vegetation in the interfluvium and and to evaluate the similarity of the flora between the types of vegetation. The data were obtained from 10 inventory studies of the flora carried out in the Napo-Putumayo-Amazonas interfluvium. A similarity analysis (ANOSIM) was performed of the flora. A model of the spatial distribution of the vegetation units was generated based on three geomorphometric parameters, which were calculated from a digital elevation model (with images from the Palsar sensor of the Alos satellite) and integrated with spectral data (from the optical images from the Sentinel satellite 2) and official spatial data. In total, 1,807 species corresponding to 140 plant families were found. There are seven types of vegetation, the largest corresponding to the high terrace forest, low hill forest and high hill forest. The plant community between the terra firme forest and the flooded forest were different according to the similarity analysis (p-value = 0.001); the species more associated with flooded forests are Oxandra euneura Diels, Mauritia flexuosa L. f., Euterpe precatoria Mart, Cynometra spruceana Benth., Pouteria gomphiifolia, Tovomita laurina Planch. & Triana and Macrolobium limbatum Spruce ex Benth.